Accuracy Assessment of “Step-by-Step” Simulation Modeling Method for Rock Breaking by TBM Disc Cutters Assisted with Laser - Zhang, Kui; Kuang, Minghai; Liu, Jingang; Zheng, Xuejun; Qiao , Shuo (Periodica Polytechnica Civil Engineering, 2023)
Rock breaking by laser-assisted disc cutters is a novel high-efficiency rock breaking mode that combines mechanical stress induced by the disc cutters with thermal cracking by laser. This paper presented a “step-by-step” simulation modeling concept, and conducted an in-depth study on potential influencing factors of simulation accuracy at each key step. First, the prediction accuracy of laser holes in laser drilling simulation was discussed. Second, the SHPB simulation and experiment were carried out to evaluate the accuracy of the selected material constitutive model in simulating the dynamic fracture damage of rock. Then, taking the laser-assisted rock-penetrating process of the scaled disc cutter as an example, the simulation prediction accuracy of rock-breaking by the disc cutter was analyzed. Finally, the simulation and experiment of laser-assisted disc cutter penetration into rock was carried out, and then the feasibility of the “step-by-step” concept was analyzed. The results show that: (1) in the laser drilling simulation, the predicted accuracy of laser hole size is higher when the power is low; with the laser power increases, the large amount of glass glaze will affect the subsequent modeling accuracy; (2) the HJC model can be used to simulate the transient nonlinear fracture damage behavior of granite; (3) the damage morphology of the granite obtained by the penetration simulation is highly similar to the experimental results, and the load curve should be corrected by the peak point fitting method. The results show the application prospects of the proposed numerical modeling method in future laser-assisted TBM tunnelling.